The Oxford companion to the English language - McArthur, Tom (Thomas Burns) (Oxford Oxford University Press, 1992)
Thirty-five hundred entries offer information of writing and speech, linguistics, rhetoric, literary terms, and related topics. Contains a chronology of English and Roman times to 1990, and an index of people who appear in entries, and biographies of influential figures such as Noah Webster and Noam Chomsky.
Keywords: English philology -- Encyclopedias. Language and languages -- Encyclopedias. Lenguaje e idiomas -- Enciclopedias y diccionarios